The AROMHA brain health test is a remote olfactory assessment to screen for cognitive impairment - Benoît Jobin; Colin Magdamo; Daniela Delphus; Andreas Runde; Sean Reineke; Alysa Alejandro Soto; Beyzanur Ergun; Sasha Mukhija; Alefiya Dhilla Albers; Mark W. Albers (Scientific Reports)
Abstract Cost-effective, noninvasive screening methods for preclinical Alzheimer’s disease (AD) and other neurocognitive disorders remain an unmet need. The olfactory neural circuits develop AD pathological changes prior to symptom onset. To probe these vulnerable circuits, we developed the digital remote AROMHA Brain Health Test (ABHT), an at-home odor identification, discrimination, memory, and intensity assessment. The ABHT was self-administered among cognitively normal (CN) English and Spanish speakers (n = 127), participants with subjective cognitive complaints (SCC; n = 34), and mild cognitive impairment (MCI; n = 19). Self-administered tests took place remotely at home under unobserved (among interested CN participants) and observed modalities (CN, SCC, and MCI), as well as in-person with a research assistant present (CN, SCC, and MCI). Olfactory performance was similar across observed and unobserved remote self-administration and between English and Spanish speakers. Odor memory, identification, and discrimination scores decreased with age, and olfactory identification and discrimination were lower in the MCI group compared to CN and SCC groups, independent of age, sex, and education. The ABHT revealed age-related olfactory decline, and discriminated CN older adults from those with cognitive impairment. Replication of our results in other populations would support the use of the ABHT to identify and monitor individuals at risk for developing dementia.